Aplikasi Pengarsipan Surat Menyurat Berbasis Web menggunakan Metode First Come First Serve dan White Box Testing - Muhammad Nurdin; Fauziah Fauziah; Ratih Titi Komalasari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The existing mail management or archiving process still uses conventional or manual management with a search process that uses a long time, so researchers create a correspondence archive application that is considered necessary and help the Administration, using FCFS method and program code logic test using white Box Testing. The purpose of making this archival application is to help administrative officers to conduct digital management of mail archives. Black box test results show every design and control function in the application according / valid and white box test results show the calculation of logic flow that produces cyclomatic value, node, predicate node and existing path value produce the same value for page login value Cyclomatic Complexity, Predicate Node (P), and Path-path = 2, while for testing white box in the mail transaction section produces the same value that is for the value of Cyclomatic Complexity, Predicate Node (P), and Path-path = 3, so it can be concluded that the logic flow used is appropriate and can be implemented in The Administration.